A study on Mechanical Properties of Polylactic Acid (PLA) reinforced with kenaf fiber mat biocomposite - Sau, Wan Ting (2020)
Kenaf fiber mat (KFM) reinforced polylactic acid (PLA) biocomposite have been developed by using film stacking and compression molding. The PLA has limitation such as brittleness and high costing. Therefore, to achieve the composite with good mechanical properties, the effect of processing parameters such as processing temperature and heating time on mechanical properties of PLA was studied. The optimum processing temperature and heating time was then being used to produce PLA/KFM biocomposite. On the other hand, PLA and fiber has distinct properties as natural fiber is hydrophilic whereas the polymer matrix is hydrophobic. In order to improve the fiber matrix adhesion, the KFM was chemically treated at different concentrations such that 0%,2%, 4%, 6% and 8% concentration of alkaline for 3 hours at room temperature. Fourier Transform Infrared (FTIR) was used to investigate the changes of fiber after alkali treatment. FTIR results showed that the lignin and hemicellulose were effectively removed from the fiber after chemical treatment. Besides that, mechanical properties such as tensile and flexural strength, tensile and flexural modulus and elongation at break of untreated and alkali-treated PLA/KFM biocomposite were studied and compared. The results obtained showed that the alkali treatment have impact on the mechanical properties of PLA/KFM biocomposite. The study has demonstrated the optimum alkali concentration was 4% NaOH concentration. This was clarified further by SEM where the adherence between the fiber and matrix was improved when the KFM was treated by 4% NaOH concentration.